Atrocities against scheduled castes and scheduled tribes - Narwani, G. S. (Rawat Publications, 2011)
While drafting the Constitution of India, Dr. B.R. Ambedkar made an earnest effort to ensure equality to all Indian citizens, including Dalits - a marginalized group in Indian society - with a view to bring about a society free from exploitation of all kinds. Besides Article 17 of the Constitution, which abolished 'untouchability,' special laws - such as the PCR Act, 1955, and the Prevention of Atrocities against SC/ST Act, 1989 - were also enacted to ensure this. What types of atrocities still continue in Indian society? Are the laws ineffective? Are there administrative lapses? In this book, social, political, administrative, legal, and other aspects have been analyzed, along with a look at the ways forward in making these laws effective.